If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3(k-5)-2(k+1)-13=-22
We move all terms to the left:
-3(k-5)-2(k+1)-13-(-22)=0
We add all the numbers together, and all the variables
-3(k-5)-2(k+1)+9=0
We multiply parentheses
-3k-2k+15-2+9=0
We add all the numbers together, and all the variables
-5k+22=0
We move all terms containing k to the left, all other terms to the right
-5k=-22
k=-22/-5
k=4+2/5
| 3(x-3)1-2x=11 | | (3x+6/3)-(4x/x-3)=x | | 4m^2-12m+5=0 | | 8=16=8n | | 2x-1/2=3/2+1/2 | | x/5+5=-3 | | 3(z+1)-2=3z+1 | | 100000/1.25=x | | 2z^2+3z+9=0 | | 7y+4.3=60.3 | | 7x+7=5x+4 | | 2x2+3x-5=0 | | u2+6u+12=0 | | (3/4)*(3+2x)+1=13 | | 3c^2-2c-32=0 | | u^2+6u+12=0 | | 3/4(3+2x)+1=13 | | 2a+2=-3+12 | | 2(w+3)=-6(w+7) | | -3v-5(v-8)=7(12-8v)+4v | | 61=23^x | | 2=2+6-2x | | 4x^-9x-100=0 | | Y^2-60+12y=0 | | 2(w+3)=-6(w+7 | | 1/2y+5−3/4y=0 | | 0.75x+0.2x=x-3.5 | | -3=x+x+1+x+2 | | 3|2x+1|=12 | | -2x+4=4x-1 | | 45(p^2-1)=56 | | -(1-3p)=-(1+6p) |